The Role of Environmental Law in Encouraging Reducing the Use of Plastic Waste in Indonesia - Vigopang, Grenaldus Calvino; Yudhistira, Dhiwatsani; Tanuwijaya, Jhonatan (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Indonesia is one of the countries with the largest waste producer in the world, Indonesia is listed as one of the largest contributors to marine plastic waste in the world. It is recorded that the amount of plastic waste from Indonesia into the oceans reaches 56,333 metric tons every year. This is due to the excessive use of plastic waste and the ineffective decomposition of plastic waste in Indonesia. This study aims to analyze the role of environmental law in encouraging the reduction of the use of plastic waste in Indonesia by using the library study method. This research was conducted by collecting and analyzing various literature sources related to plastic waste and the role of environmental law in reducing plastic waste in Indonesia. Library sources used include journals, books, papers, conferences, and related legal documents. The results of the analysis show that the role of environmental law in encouraging the reduction of the use of plastic waste in Indonesia is still not effective. The presence of environmental law has not been able to be a solution to overcome the problem of plastic waste in Indonesia. Through this literature study, efforts can be made to reduce the population of plastic waste in Indonesia by using various methods, ranging from the use of regulations and regulations, and ways of processing plastic waste that can be done to reduce the amount of plastic waste in Indonesia.